skulptur projekte münster 07 - Franzen, Brigitte; König, Kasper; Frangenberg, Frank; Gaskins, Matthew; Gründer, Annkatrin; Landesmuseum für Kunst und Kulturgeschichte, Münster (Köln : König, 2007)
Ben-Ner, Guy ; Boyce, Martin ; Gonzalez-Foerster, Dominique ; Lehanka, Marko ; Meyer, Eva ; Narkevicius, Deimantas ; Philipsz, Susan ; Schaerf, Eran ; Siekmann, Andreas ; Wagner, Silke ; Wedemeyer, Clemens von ; Wehrmann, Annette
Althamer, Patel ; Deller, Jeremy ; Genzken, Isa ; Garcia, Dora ; Asher, Michael ; Baghramian ; Naira ; Bijl, Guillaume ; Deller, Jeremy ; Genzken, Isa ; Greenfort, Tue ; Kelley, Mike ; Metzger, Gustav ; Nauman, Bruce ; Pask, Maria ; Schütte, Thomas ; Trockel, Rosemarie ; Jouve, Valerie ; Rosler, Martha ; Wallinger, Mark ; White, Pae
Tentoonstelling, LWL-Landesmuseum für Kunst und Kulturgeschichte, Münster, 17.06.07-30.09.07
boek